Renewable Energy Consumption in Somalia: Assessing Its Impact on Currency Exchange Rates - Mohamud, Iqra Hassan; Warsame, Zakarie Abdi; Mohamud, Ahmed Abdirashid; Hassan, Abas Mohamed; Mohamud, Ibrahim Hassan (International Journal of Energy Economics and Policy, 2024)
This study utilizes an Autoregressive Distributed Lag (ARDL) model to examine the effects of renewable energy, economic growth, and inflation rate on exchange rate fluctuations in Somalia from 1990 to 2019. The analysis shows that economic growth and RE positively influence the exchange rate in both the short and long run. In contrast, inflation negatively impacts the exchange rate in the short run, suggesting short-term currency appreciation, but leads to depreciation in the long term. Moreover, the study finds that a 1% increase in RE results in an 80% increase in the exchange rate, indicating significant currency depreciation. To mitigate currency depreciation, the research advocates for policies promoting local renewable energy use to reduce import dependency and stabilize the currency. This approach includes investments in renewable infrastructure, community education, and economic diversification. This study highlights the need for further research into renewable energy’s impact on exchange rates in Somalia, particularly in different economic contexts, to gain a more holistic understanding of these dynamics.